The Effect of Using McCarthy Model in Improving Reflective Thinking and Science Achievement for Grade 6th Basic Female Students - Alhadaybeh, Eman; Ambusaedy, Abdullah (Jordan Journal of Educational Sciences, 2016)
This study aimed to investigate the effect of using McCarthy Model in development reflective thinking and science achievement among grade 6th female students. The sample of study consisted of (55) female students, which were selected from two schools in Dakhiliyah Governorate. The experimental group (N=31) was taught the science content by McCarthy Model and control group (N=24) was taught the by the conventional method of teaching. To achieve the study’s aims, three research instruments were designed: a teacher guide based on McCarthy Model, a reflective thinking skills test and a science achievement test. The results revealed that there were statically significant differences at (α=0.05) between the means of the experimental group and the control group in the whole reflective thinking skills and in the whole science achievement test in favor of the experimental group